Statistics as the articulator of health problems in the speech of the PAHO and in Argentina (1923-1975 - Librandi, Juan Martín (Universidad Nacional del Litoral, 2020)
The article reconstructs the way in which statistics participated in the problematization of health by the Pan American Health Organization (PAHO) between 1923 and 1975. To do this, we analyze in PAHO's discourse the different conceptions of health statistics, their functions, bureaucratic structures, and how these were related to the development of statistical devices in the region. We identify two different conceptions in PAHO's discourse: a) health as a problem linked to trade regulations; and b) health as a requirement of the economic development of nations. In turn, we conclude that health statistics was a significant component of PAHO's intervention in regional health policy.